Prescrizione del reato: principi costituzionali, patologie e recenti riforme - Cavaliere, Antonio (Cultura giuridica e diritto vivente, 2021)
[Statute of limitations: constitutional principles, pathologies and recent reforms] This paper concerns the ‘statute of limitations’ rules in Italian criminal law. It aims to show the connection between the legal rules and some constitutional principles of punishment and criminal procedure. Further, it analyses the most important factors that cause the malfunction of those rules and it criticizes the recent reform acts 2017 and 1029